Pengembangan Literasi Finansial melalui Kegiatan Pengabdian Masyarakat dalam Bentuk Pengenalan Pasar Modal bagi Siswa SMKN 1 Pantai Cermin - Abdul Muttaqin Rusydi; Lulu Syabrina; Nona Pebriana Rangkuti; Zahratul Idami (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Community service is an integral part of the Tri Dharma of Higher Education that must be carried out by university students. The 2025 KKN UINSU Desa Celawan program at SMKN 1 Pantai Cermin was designed to make a real contribution through the development of financial literacy based on the introduction of the capital market. This program was motivated by the low level of financial management and investment understanding among vocational school students. Therefore, the students organized a socialization and education program in collaboration with the Indonesia Stock Exchange (IDX) North Sumatra Representative and the Islamic Capital Market Study Group (KSPMS) Golden UINSU. The implementation method consisted of several stages: permission submission, site observation, proposal preparation, socialization activities, and evaluation through discussion and Q&A sessions. The activity, held on Monday, August 25, 2025, was attended by 50 students, mostly from the accounting major, in an interactive atmosphere involving presentations, simulations, and direct discussions. The results indicated an increase in students’ understanding of basic capital market concepts, differences between legal investments and illegal practices, as well as the initial steps to open a securities account. Students’ responses were highly positive, marked by their enthusiasm in asking questions and engaging in discussions. This program provided reciprocal benefits: for students as financial literacy provision, and for KKN students as valuable experience in public communication and community service. In conclusion, capital market socialization is a strategic means of building a financially literate young generation ready to face future economic challenges.